A Comparative Study of LSB based Statistical Steganalysis and Gray Level Co-Occurrence Matrix based Blind Image Steganalysis - Ranjan Ghosh, Bibek (International Journal of Computer Sciences and Engineering, 2022)
Image steganography is used as a covert communication technique which hides secret data in cover image intelligently so that it is visually imperceptible. This is often used by individual or organization with bad intent to harm people, organization or society. Steganalysis technique is used to break these systems to extract the secret information, reveal such covert communication and thwart imminent threat. Steganalytic techniques can be broadly classified as targeted or blind. In the former the knowledge of steganographic system used should be known and the latter adopts a more general approach where no knowledge of the process used to hide data is required. This paper studies some well-established statistical methods of targeted steganalysis and gray level co-occurrence matrix based blind steganalysis and compare their performances.